Dual Differentiation-Exogenous Mesenchymal Stem Cell Therapy for Traumatic Spinal Cord Injury Repair in a Murine Hemisection Model - Hai Liu; Edward M. Schwarz; Chao Xie (Stem Cells International)
Mesenchymal stem cell (MSC) transplantation has shown tremendous promise as a therapy for repair of various tissues of the musculoskeletal, vascular, and central nervous systems. Based on this success, recent research in this field has focused on complex tissue damage, such as that which occurs from traumatic spinal cord injury (TSCI). As the critical event for successful exogenous, MSC therapy is their migration to the injury site, which allows for their anti-inflammatory and morphogenic effects on fracture healing, neuronal regeneration, and functional recover. Thus, there is a need for a cost-effective in vivo model that can faithfully recapitulate the salient features of the injury, therapy, and recovery. To address this, we review the recent advances in exogenous MSC therapy for TSCI and traumatic vertebral fracture repair and the existing challenges regarding their translational applications. We also describe a novel murine model designed to take advantage of multidisciplinary collaborations between musculoskeletal and neuroscience researchers, which is needed to establish an efficacious MSC therapy for TSCI.